2018
DOI: 10.3390/cells7040032
|View full text |Cite
|
Sign up to set email alerts
|

CDK5RAP2 Is an Essential Scaffolding Protein of the Corona of the Dictyostelium Centrosome

Abstract: Dictyostelium centrosomes consist of a nucleus-associated cylindrical, three-layered core structure surrounded by a corona consisting of microtubule-nucleation complexes embedded in a scaffold of large coiled-coil proteins. One of them is the conserved CDK5RAP2 protein. Here we focus on the role of Dictyostelium CDK5RAP2 for maintenance of centrosome integrity, its interaction partners and its dynamic behavior during interphase and mitosis. GFP-CDK5RAP2 is present at the centrosome during the entire cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Wide-field fluorescence microscopy was performed as described previously [20], using either a Zeiss Axiovert 200 M system equipped with a mercury-halide lamp (Zeiss HXP120), a PlanApo 1.4/100× objective, an Axiocam MRm Rev.3 charge-coupled device (CCD) camera and Axiovision 4.8 software or an Axioobserver System equipped with an LED light source (Zeiss, Colibiri 7), a PlanApo 1.4/100× objective, an Axiocam 506 mono, a piezo stage and ZEN Blue Software (Carl Zeiss Mikroskopie GmbH, Jena, Germany). Deconvolution was performed with the mentioned software packages essentially as described previously [23]. Expansion microscopy (ExM) samples were prepared as described previously [9].…”
Section: Light Microscopymentioning
confidence: 99%
“…Wide-field fluorescence microscopy was performed as described previously [20], using either a Zeiss Axiovert 200 M system equipped with a mercury-halide lamp (Zeiss HXP120), a PlanApo 1.4/100× objective, an Axiocam MRm Rev.3 charge-coupled device (CCD) camera and Axiovision 4.8 software or an Axioobserver System equipped with an LED light source (Zeiss, Colibiri 7), a PlanApo 1.4/100× objective, an Axiocam 506 mono, a piezo stage and ZEN Blue Software (Carl Zeiss Mikroskopie GmbH, Jena, Germany). Deconvolution was performed with the mentioned software packages essentially as described previously [23]. Expansion microscopy (ExM) samples were prepared as described previously [9].…”
Section: Light Microscopymentioning
confidence: 99%
“…Concerning cell motility, an uninterrupted series of studies in the last 50 years has led to the identification and characterization of the acto-myosin cytoskeleton underlying changes in cell shape and cell motility processes, with many cytoskeletal proteins first identified and/or characterized in Dictyostelium, such as coronin, the actin nucleator SCAR, the 34-kDa actin-crosslinking protein, myosin I and II, and formins (see Bozzaro, 2013 for references). The dynamic structure of the cell cortex, the actin cytoskeleton-nuclear membrane interactions, nucleus/nucleolus and the microtubule cytoskeleton, and their regulation by small GTPases have been the subject of several studies also in recent years (Nichols et al, 2015;Gräf et al, 2015;Rivero and Xiong, 2016;Meyer et al, 2017;Pitzen et al, 2018). Recently, the role of formins in regulating the functional integrity of the cell cortex has been investigated in detail (Junemann et al, 2016), and it has been shown that the HSBP1 protein, which regulates WASH complex assembly at centrosomes, is required for development of focal adhesion and cell polarity in Dictyostelium as well as in tumour cells (Visweshwaran et al, 2018).…”
Section: Past and Present Of A Model Organismmentioning
confidence: 99%
“…The latter then replaced centrioles as the core duplicating structures after their loss due to their dispensability in non-motile or amoeboid cells. As highlighted in their paper and also in the contribution of Pitzen et al in this issue of Cells [ 37 ], CDK5RAP2 and its orthologues play a key role as PCM scaffolding proteins for γ-tubulin complexes in this context. Yet, the concept that centriole-containing centrosomes are most likely more ancestral than acentriolar centrosomes not at all devalues research on model organisms possessing no centrioles.…”
Section: Evolution Of Centrosomal Structuresmentioning
confidence: 99%
“…Due to the extremely high affinity of the streptavidin-biotin interaction, BioID only rarely brings up false positive interactors. In centrosome research this robust method was applied in mammalian cells and Dictyostelium amoebae with great success [ 37 , 61 , 62 , 63 , 64 ]. In mammalian cells, these analyses also revealed a molecular relationship between so-called centriolar satellites, i.e., microscopically visible proteinacious granules of the pericentrosomal area.…”
Section: Recent Developmentsmentioning
confidence: 99%
See 1 more Smart Citation